MDMA, Love, Mourning and Melancholy. Experiences of Psychological “Compression” - Fallon, Finian (Leitura Flutuante, 2013)
This article is an exploration of the experience of working with young adult clients who have been traumatised as a result of misusing MDMA, often combined with alcohol. A single overdose may lower psychological defences and prevent the ability to achieve a healthy repression of unconscious conflicts, resulting in an immediate or delayed existential crisis. In response there may be what is described by the author as “compression” where euphoria and dis-inhibition combine to overwhelm the psyche. The paper also explores the current use of MDMA in PTSD research and its location in contemporary culture. It incorporates Freud’s perspective from Mourning and Melancholia into the clinical approach to working with this cohort, including perspectives on mourning, loss, narcissism and displaced reproach. The compression experience may be temporarily suppressed only to emerge in depressive symptoms and suicidal ideation.